Analisis Pengaruh Implementasi E-Learning Vilep di Poltekkes Kemenkes Palembang dengan Pendekatan EUCS - Dien Novita (Lembaga Penelitian dan Pengabdian pada Masyarakat (LPPM) STMIK Global Informatika MDP, 2020)
E-Learning Vilep is a support system in the teaching and learning process that is in Poltekkes Kemenkes Palembang. The purpose of this research is to determine the level of user satisfaction in using Vilep e-learning at the Poltekkes Kemenkes Palembang by using the End User Computing Satisfaction (EUCS) satisfaction model which consists of five factors, namely: content, accuracy, form (format), ease of use, and timeliness. The process of collecting data is done by conducting interviews, observations, and distributing questionnaires to Vilep e-learning users. The sampling technique uses a random sample using the Slovin formula with a sample size of 352 respondents. Data processing using SPSS and Excel. The results of the research indicate that the level of user satisfaction Vilep e-learning simultaneously shows all the variables are significant, and seen from the correlation analysis obtained R2 0,854 shows that the satisfaction variable can be explained by the content, accuracy, format, ease of use and timeliness variables 85, 4%.